Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Yang Terdaftar Di Indeks LQ45 Bursa Efek Indonesia Periode 2016-2018 - Triadi Viriya Cuaca; Saifhul Anuar Syahdan (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to examine empirically about the influence of company’s size, profitability, leverage, likuidity, public shareholders and growth to the disclosure of corporate social responsibility of LQ 45 index companies listed in the Indonesia Stock Exchange in the periode of 2016-2018 simultaneously and partially. This study was a study with a quantitative approach and the data used were the secondary data. The number of population for this research is 45 companies and the number of sample is 21 companies with purposive sampling technique. The data analysis used was multiple linear regression. The results showed that simultaneous independent variables are company’s size, profitability, leverage, liquidity, public shareholders and growth has significant influence to corporate social responsibility disclosure. While partially, indicate that independent variables profitabillity, public shareholders, and growth has significant influence to dependent variable corporate social responsibility disclosure and independent variables company’s size, leverage, and liquidity has no significant influence to dependent variable corporate social responsibility disclosure.